PROFIL KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI IKATAN KIMIA - Khoirunnisa, Fitriah; Sabekti, Ardi Widhia (Universitas Pendidikan Ganesha, 2020)
The purpose of this study is to analyze students' critical thinking skills in the Chemistry Bond subject. This research is quantitative research with a descriptive approach. The participant of this research were 190 grade X and XI students from several high schools in Tanjungpinang city. The sampling technique was done by purposive sampling at several schools accredited A and B by BSNP. Data collection techniques used 8 test instruments representing 4 aspects of critical thinking, including aspects of providing explanations, building basic skills, managing strategies-tactics, and concluding. Classically, the critical thinking ability of high school students Tanjungpinang city on the Chemical Bond subject is still relatively low with average score is 34.45.